Isolation and Identification of Shigella sp. in Cattle Feces in Tamangapa Final Disposal Place, Makassar City - Ardat, Dwi Arini Ardat; A. Magfirah Satya Apada; Muh. Danawir Alwi; Irwan Ismail; Zainal Abidin Kholilullah (Jurnal Riset Veteriner Indonesia (Journal of The Indonesian Veterinary Research), 2023)
Beef cattle are one of the most widely developed types of fauna by the people of Indonesia because they are supported by Indonesia's land area which reaches 1,922,570 km² and has a favorable climate, namely a tropical climate. However, this does not apply to urban areas where limited grazing land is one of the reasons urban breeders graze cattle in final disposal site (TPA) as is done by the people around the Tamangapa TPA, Makassar City. One of the impacts of grazing cattle in the final disposal site is contamination of the cow feed with various microorganisms such as Shigella sp bacteria which can cause shigellosis. Shigellosis is a zoonotic disease and can be transmitted through contaminated food such as raw eggs, raw meat, vegetables or from contaminated water. Diarrhea in toddlers 26.7% is caused by Shigella sp. This study aims to isolate and identify Shigella sp. in cow feces at the Tamangapa final disposal site (TPA) in Makassar City. The samples taken were 28 samples from 17 farms around the TPA Tamangapa Makassar City. Samples that have been taken are then stored in a transport medium and then the isolation and identification process is carried out using Nutrient Agar (NA) media, gram staining, Salmonella Shigella Agar (SSA) and biochemical tests which include TSIA, SIM, MR-VP, urease and citrate. The results showed the level of infection with Shigella sp. in the feces of cows grazed around the TPA Tamangapa Makassar City was low where of the 28 stool samples tested, only 2 samples (7%) were positively contaminated with Shigella sp